Strengthening Junior High School Members in Maros Regency in Supporting Adiwiyata Schools - Naimah Aris; Jusmawati Massalesse; Nur Erawaty; Nurdin Nurdin; Kasbawati Kasbawati; Edy Saputra; Anisa Anisa; Anna Islamiyati; Sri Astuti Thamrin; Sitti Sahriman; Ainun Mawaddah Abdal; Najhah Aris; Muralia Hustim; Afifah Afifah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Maros Regency as an area that often receives Adipura award certificates should have schools that are also capable of achieving the Adiwiyata school title, a program that collaborates education with the environment. However, according to partners, out of 76 junior high schools in Maros Regency, only 5 have received this award. Starting from this, a team of lecturers from the Mathematics, Statistics, and Environmental Engineering study programs in collaboration with the Center for Development and Control of the Sulawesi and Maluku Ecoregions held training and mentoring activities for junior high schools in Maros Regency so that they were able to get the adiwiyata school title. Several aspects of the adiwiyata school assessment include curriculum development and environment-based learning, in this case specifically for mathematics. Organize the management of land, facilities and infrastructure in the environment around the school, in order to create an atmosphere that contributes to the formation of the character of students who are environmentally sound, build an extra-curricular climate that can contribute to environmental conservation, provide creativity and innovation for school residents in environmental protection and management efforts. The target audience for this service are students, teachers, and the junior high school environment in Maros Regency. The training activities was take place at SMP Negeri 16 Mandai, Maros Regency. The methods used include lectures, FGDs accompanied by demonstrations/practices, as well as monitoring and evaluation in class.